Efecto de aceites esenciales en emulsión en el control de ninfas de bactericera cockerelli, en condiciones de laboratorio, provincia de Cotopaxi, cantón Latacunga. - Acosta Segovia, Catherine Belén (2023)
Bactericera cockerelli is a pest that can reproduce losses of up to 100% of the production in Solanaceae due to its rapid dissemination in crops, which has forced farmers to take control measures based on frequent applications and excessive chemical products; therefore, each day, they are looking for alternatives to replace these to solve the problem. This research was carried out in the Entomology laboratory of the Technical University of Cotopaxi. Its objective was to evaluate the effect of essential oils in the emulsion on Bactericera cockerelli nymphs at three concentrations of 25% and 50%, including the control 0%, where a Completely Random Design (CRD) was applied with an A*B factorial arrangement with six treatments and three repetitions; in each treatment, 20 individuals of the species and state under study were released where the essential oils were applied in the emulsion. Mortality data was collected by observation two minutes after applying the treatments, using counting and extracting dead individuals. In the same way, the compositional analysis of the oils under study was carried out by means of gas chromatography. From the results obtained, it was determined that the compounds with the highest presence are 2-un decanone with 46.88% and Trans-Anetol with 75.88% in Ruta graveolens and Anethum graveolens, respectively. It was also established that the essential oils in emulsion control Bactericera cockerelli nymphs under laboratory conditions, with an average of 11.44 individuals killed by Ruta graveolens and 3.37 individuals killed by Anethum graveolens. For the interaction between oils*concentrations, Ruta graveolens, in a 50% concentration, presented an average of 17.67 dead individuals during the two minutes of oil application in the emulsion.